Innovative approach to teaching mathematics using data analytics - Gavrilović Branko M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2023)
With the development of information technology, the Internet, and social networks, the amount of collected data is growing year by year at a high rate. Data processing and analysis becomes a necessity without which quality decisions cannot be made. Education, as an important social segment, must follow global changes and provide an adequate response to new social needs. International tests have shown that students from Serbia have problems with processing and analyzing data as well as applying mathematical knowledge in modeling real-life situations. In this paper, an innovative approach to teaching mathematics based on data analytics will be presented. The goal of the paper is to show the possibility of using data analytics techniques in the teaching process. A teaching model using data analytics will be presented, as well as a complete preparation for the realization of a mathematics class. By building a mathematical model using data analytics, students will gain new knowledge in the field of financial mathematics. The possibility of using data analytics in the implementation of other teaching units in mathematics, as well as in the teaching of other subjects, will be presented.